2007
DOI: 10.1002/cne.21362
|View full text |Cite
|
Sign up to set email alerts
|

Axonal regeneration and development of de novo axons from distal dendrites of adult feline commissural interneurons after a proximal axotomy

Abstract: Following proximal axotomy, several types of neurons sprout de novo axons from distal dendrites. These processes may represent a means of forming new circuits following spinal cord injury. However, it is not know whether mammalian spinal interneurons, axotomized as a result of a spinal cord injury, develop de novo axons. Our goal was to determine whether spinal commissural interneurons (CINs), axotomized by 3-4-mm midsagittal transection at C3, form de novo axons from distal dendrites. All experiments were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
1

Year Published

2009
2009
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 52 publications
3
43
1
Order By: Relevance
“…All surgical procedures were performed on adult cats (Ͼ11 months of age) under deep general anesthesia using either isoflurane (recovery experiments) or sodium pentobarbital (terminal experiments). Surgical procedures, peripheral nerve stimulation protocols, and postoperative care procedures were identical to those used in previous experiments (Fenrich et al, 2007). Briefly, for the recovery surgeries, the animal was anesthetized, and the dorsal C2 and C3 vertebrae were exposed and removed to access the C3 segment.…”
Section: Surgeriesmentioning
confidence: 99%
See 4 more Smart Citations
“…All surgical procedures were performed on adult cats (Ͼ11 months of age) under deep general anesthesia using either isoflurane (recovery experiments) or sodium pentobarbital (terminal experiments). Surgical procedures, peripheral nerve stimulation protocols, and postoperative care procedures were identical to those used in previous experiments (Fenrich et al, 2007). Briefly, for the recovery surgeries, the animal was anesthetized, and the dorsal C2 and C3 vertebrae were exposed and removed to access the C3 segment.…”
Section: Surgeriesmentioning
confidence: 99%
“…We confirmed that all lesions transected the midline through the central canal after the terminal experiments (see below). The lesion protocol has previously been described in detail (Fenrich et al, 2007) and was performed using a specially designed double-edged scalpel blade that was mounted to a motorized microdrive. Briefly, the knife was inserted to a depth of at least 5 mm (the most ventral aspect of the ventral horns is ϳ4 mm below the dorsal surface of the spinal cord at C3) (supplemental Fig.…”
Section: Surgeriesmentioning
confidence: 99%
See 3 more Smart Citations